2022
DOI: 10.32604/jrm.2022.017848
|View full text |Cite
|
Sign up to set email alerts
|

The Use of as Natural Coagulant in Algerian Drinking Water Treatment Plant

Abstract: The purpose of this work is the study the ability of the plant material Aloe vera to act as natural coagulant using raw water obtained from a drinking water treatment plant (Mila, Algeria). Different solvents such as: NaCl; NaOH and HCl were used as chemical activators to extract the active components from the Aloe vera plant, and different coagulation-flocculation experiments were conducted in a jar test apparatus to evaluate the performance of the extracted coagulant. Also, the effect of coagulant dose on so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…In general, the extraction of bio-coagulants from plants is achieved by three steps: (i) mechanical and physical treatments; (ii) extraction of the coagulant agent by using distilled water [11], either a saline solution [12][13][14][15][16] or a suitable solvent (i.e., acid or base) [13,17]; (iii) purification of the coagulant agent. This agent can belong to carbohydrates, proteins, flavonoids, tannins, total phenolics or cellulose, depending on the plant used to extract the active agent [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the extraction of bio-coagulants from plants is achieved by three steps: (i) mechanical and physical treatments; (ii) extraction of the coagulant agent by using distilled water [11], either a saline solution [12][13][14][15][16] or a suitable solvent (i.e., acid or base) [13,17]; (iii) purification of the coagulant agent. This agent can belong to carbohydrates, proteins, flavonoids, tannins, total phenolics or cellulose, depending on the plant used to extract the active agent [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…With an initial turbidity value of 424 NTU, there was a considerable decrease in turbidity value of 96.99%, resulting in a final turbidity value of 12.75 NTU at a dose of 0.5 ml and a stirring time of 10 minutes. Previous research also showed that the addition of LB-HCl coagulant can remove turbidity values with removal efficiency between 59.23% to 85.15% [12]. As shown in Figure . 6 3, the addition of LB-HCl coagulant to well water resulted in a significant decrease in turbidity values [13].…”
Section: Optimisation Of Phmentioning
confidence: 71%
“…The peak at 2922.28 cm −1 is attributed to the –CH 2 stretching vibration of the alkyl group. The peak at 2349.75 cm −1 is responsible for C N stretching [ 40 ]. A bending vibration at 1596.42 cm −1 confirmed the existence of water.…”
Section: Resultsmentioning
confidence: 99%